Reproductive seasonality of the Antarctic sea pen Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Sahade, Ricardo Jose (PLOS ONE)
The pennatulid Malacobelemnon daytoni is one of the dominant species in Potter Cove, Antarctica. Its abundance and range of distribution have increased in recent years probably related to climate change mediated alterations of environmental factors. This work is the second part of a study dealing on the reproductive ecology of Malacobelemnon daytoni, and aims to assess its reproductive seasonality over a two-year period. Sampling was carried out every month during 2009-2010 and samples were examined by histological analysis. Gametogenesis exhibited a seasonal pattern evidenced by the maturity stage index (MSI) and the number of mature oocytes and cysts throughout the year. Immature oocytes and spermatocytes were present year-round, but maturation was seasonal and it seems that more than one spawning per year was possible. These spawnings could be more linked with suspended particulate matter (SPM) (probably available via resuspension events) than with primary production pulses. This idea reinforces the hypothesis that winter time is not so stressful, in energy terms, in Potter Cove, which seems to depend on energy sources other than local phytoplankton production. There was not a strong inter-annual variability between the reproductive characteristics analyzed in 2009 and 2010; the only variable different was the size of oocytes (higher in 2009), suggesting different energy availability in each year, related with a higher concentration of SPM in 2009 (although it was not significant). Malacobelemnon daytoni could be the first reported Antarctic suspension feeder species that presents a reproductive cycle with more than a spawning event per year. This strategy would help to explain the success of this species in the Potter Cove ecosystem and in high ice-impacted areas. Fil: Servetto, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas ...